KEBIJAKAN INVESTASI, PENDANAAN DAN DIVIDEN TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Muhammad Zul Fauzan (PT Sanagi Edu Konsultan, 2025)
This study attempts to examine the impact of investment, financing, and dividend policies on the determinants of firm value on the Indonesia Stock Exchange. The population of this study was public companies listed on the Indonesia Stock Exchange, with hotel companies serving as the sample between 2015 and 2019. Purposive sampling was used to determine the sample, resulting in a total of eight hotel companies from 2015 to 2019. Data analysis techniques used were descriptive statistics, classical assumption tests, multiple linear regression models, and hypothesis testing using SPSS 26.0 for Windows. The results of this study indicate that investment decisions have a positive and significant effect on firm value, while funding policies have a positive and significant effect on firm value. Dividend policies do not significantly influence firm value.